Leveraging Structured Data Input for Effective Chatbot Integration in Enterprises - Siqueira, Caio; Fonseca, Orlando; Ferreira, Giuliano; Leiva, Omar (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2024: Anais do XV Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2024.245343, 2024)
This paper introduces an approach for integrating structured data into chatbot applications. Utilizing our Mindmap tool, which hierarchically organizes data and maps nodes to actions, we developed an augmented JSON schema to improve chatbot contextual understanding and response accuracy. By applying the Langchain suite and Retrieval-Augmented Generation techniques, our method enhances data retrieval and processing from a vector store, significantly improving interaction relevance.